Observational constraints on the HD5980 wind-wind collision - Koenigsberger, Gloria (2022)
Analysis of spectral line profi le variations observed over 6 decades in theWolf- Rayet system HD5980 lead to the conclusion that Star A, the variable member of the system, has always dominated the wind collision zone (WCZ), contrary to suggestions that before 1994 the stronger wind belonged to its close companion, Star B.The observed variations are caused by a combination of physical occultations, wind eclipses and emission and absorption originating in the WCZ. The effects caused by the leading WCZ branch, which folds around Star B, are clearly seen as it crosses our line of sight to Star A during the secondary eclipse. These effects can inform on the WCZ velocity and density structures. We speculate that differences in line pro les at the same orbital phase but at dfiferent epochs may be linked to changes in the WCZ radiative properties. The 2017-2020 spectra indicate that HD5980 was in a higher activity state than during 2010-2015.